Sustainable mobility: concepts, approaches and reality from a deprived outskirt of the metropolitan area of Bogotá - Prada, Valentina (2024)
The aim of this article is twofold. First, it provides a brief state of the art of the international literature related to sustainable mobility. Given the great diversity of approaches that encompasses the complexity of the sustainable mobility paradigm, the second part analyzes the current challenges, hinderances and prospects for maintaining and developing sustainable mobility practices in the commune of Cazucá. This study zone is a low-income neighborhood located in the south of the metropolitan area of Bogota. It is illustrative of the socio-demographic and mobility conditions that characterize many outskirts of Latin American cities. The analysis is based on census data and the latest urban mobility survey (EMU-2019). It also relies on interviews applied to key actors of the commune and inhabitants of different profiles.